Food, Conservation, and Energy Act of 2008: Grassland Reserve Program (GRP) - Hicks, Erin, author; Seidl, Andrew, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2008)
The Grassland Reserve Program (GRP) is a voluntary program that assists farmers and ranchers to maintain grasslands as grazing land and prevent conversion of grassland into other uses, such as cropping or urban development. The program focuses on supporting working grazing operations, protecting grassland, and enhancing biodiversity through provision of habitat. Normal haying and grazing activities are allowed under GRP. Producers must also restore and maintain appropriate grasses, forbs, and shrubs and address resource concerns such as soil erosion. The 2002 Farm Bill established the GRP, which is administered jointly by the Natural Resources Conservation Service, the Farm Service Agency, and the Forest Service.
Grassland Reserve Program (GRP)
2008 agricultural and resource policy report, no. 6
October 2008.
Keywords: Grassland Reserve Program (GRP); Incentives in conservation of natural resources -- United States; Grassland restoration -- United States; Grassland conservation -- United States; Cropland conversion program -- United States; Conservation of natural resources -- United States; Natural resources -- Law and legislation -- United States; Contracts, Agricultural -- United States; Agricultural conservation -- United States; Agricultural laws and legislation -- United States; Agricultural subsidies -- Law and legislation -- United States